Behavior and Group Movement of Proboscis Monkey’s (Nasalis larvatus Wurmb.Wurmb.) in Samboja, East Kalimantan - Atmoko, Tri; Mardiastuti, Ani; Iskandar, Entang (Jurnal Penelitian Kehutanan Wallacea, 2017)
Proboscis monkey (Nasalis larvatus Wurmb.) are endemic primates to the island of Borneo that are subjected to serious problems like habitat loss, fragmentation and forest degradation. Studies of movement behavior of monkeys have been done in the isolated and fragmented habitat in Samboja, East Kalimantan. Behaviour data of feeding, moving, social, resting, and sleeping were collected using instantaneous sampling method. The plotsof trees survey were established 20 m x 200 m on each habitat. The movement behavior consists of daily ranging and utilization of height of the canopy. Daily ranging was recorded by GPS and height of canopy utilization divided to 0-3 m, 3.1-6 m, 6.1-9 m, 9.1-12 m, and > 12 m. The results showed that the daily ranging of the monkeys were varied, ranging from 25.7 m– 749.9 m (average 333 m), which home ranges between 4.52 ha – 6.92 ha. Daily movement distance between groups on the three habitat was different. Generally, the monkeys used canopy strata depending on habitat conditions, height, diameter and density of trees.